PERUBAHAN SIFAT TANAH DI BAWAH TEGAKAN Acacia mangium Wild PADA AREAL HTI PT. FINANTARA INTIGA KABUPATEN SINTANG (Properties of Soil Changes Under Acacia mangium Wild in HTI Area PT. Finantara Intiga Kabupaten Sintang) - Siti Latifah (Tengkawang : Jurnal Ilmu Kehutanan, 2011)
Estabilishment of plantation forest (HTI) is one of the land rehabilitation program in Indonesia. The goal of HTI program is to reclaim land for this purpuse. This research aims to characterize physical and chemical change in soil after the reclamation with Acacia mangium Wild. This research employed the survey method, and soil sampling was done purposively. Data were analyzed using a complete random design (RAL). Result show that there were changes in soil physical and chemical properties in area planted with Acacia mangium Wild. C-organic, N-total, K, pH, and porosity of soil increased after the HTI program. Also, soil texture getting improved. P decreased during early planting was decreased, possibly because it used in large amounts for plant growth. After the 6th year after planting the P content started to increase. This is possibly because Acacia mangium Wild partly died-off and dead plant part decomposed and released P to the soil. Keyword : Plantation forest, land rehabilitation, Acacia mangium Wild, changed, soil